End of 9-Endings, Price Recall, and Price Perceptions - Avichai Snir; Daniel Levy; Haipeng Chen (Economics Letters, 2017)
Prices that end with 9, also known as psychological price points, are common, comprising about 70% of the retail prices. They are also more rigid than other prices. We take advantage of a natural experiment to document an emergence of a new price ending that has the same effects as 9-endings. In January 2014, the Israeli government passed a new regulation prohibiting the use of non 0-ending prices, bringing an end to 9-ending prices. We find that seven months after 9-ending prices have disappeared, 90-ending prices acquired the same status as 9-ending prices had before the new regulation was adopted. Thus, 90-ending prices became the new psychological price points, partially eliminating the regulation's intended effect.
Keywords: E31; L16; K20; D40; D83; L81; M21; M31; 330; 9-ending prices; psychological price points; price recall; price perception; sticky prices; rigid prices; price rigidity; price flexibility; price stickiness; level effect; left-digit effect; image effect; right-digit effect; integer constraint; price control; price regulation